2013
DOI: 10.1016/j.ijggc.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

A statistical analysis of well production rates from UK oil and gas fields – Implications for carbon capture and storage

Abstract: . (2013) 'A statistical analysis of well production rates from UK oil and gas elds implications for carbon capture and storage.', International journal of greenhouse gas control., 19 . pp. 510-518. Further information on publisher's website:http://dx.doi.org/10.1016/j.ijggc.2013.10.012Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in International Journal of Greenhouse Gas Control. Changes resulting from the publishing process, such as peer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Mathias et al showed that the injection rate statistics from Hosa et al are very similar to bulk fluid production rates (i.e., combined volumetric rates of oil, water, and gas at reservoir conditions) from 104 offshore U.K. oil and gas fields. By averaging production rates over a 10 year period, Mathias et al showed that 50% of the production wells studied produced bulk fluid at a rate of less than 3.5 million barrels per year. Assuming a CO 2 density of 650 kg/m 3 , this volumetric rate converts to around 0.35 megaton/year.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mathias et al showed that the injection rate statistics from Hosa et al are very similar to bulk fluid production rates (i.e., combined volumetric rates of oil, water, and gas at reservoir conditions) from 104 offshore U.K. oil and gas fields. By averaging production rates over a 10 year period, Mathias et al showed that 50% of the production wells studied produced bulk fluid at a rate of less than 3.5 million barrels per year. Assuming a CO 2 density of 650 kg/m 3 , this volumetric rate converts to around 0.35 megaton/year.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…However, when many wells are 69 applied in close proximity, the pressure interference between wells causes individual injection wells 70 4 to act as if contained within completely confined saline formation units [12,13] Mathias et al [19] showed that the injection rate statistics from Hosa et al [18] are very similar to 124 bulk fluid production rates (i.e., combined volumetric rates of oil, water and gas at reservoir 125 conditions) from 104 offshore UK oil and gas fields. By averaging production rates over a ten year 126 period, Mathias et al [19] showed that 50% of the production wells studied produced bulk fluid at a likely to achieve injection rates greater than 1 Mt/year. Based on these studies, we will consider is approximately inversely proportional to the injection rate.…”
mentioning
confidence: 99%
“…In this study we consider a base case scenario of 24 MtCO 2 injection per year in the eld, which is split evenly between the 12 injection sites. While studies by Noy et al [9] and Farhat et al [22] consider higher rates of injection per site at 5 MtCO 2 /year, on average, industry practice in the North Sea would suggest an injection rate per site to be 1-2 MtCO 2 /year [44,45,40].…”
Section: Simulation Parameters and Constraintsmentioning
confidence: 99%
“…These parameters are considered to be typical of many depleted gas reservoirs around the UK continental shelf. The constant CO 2 injection rate of 0.3 Mt year −1 is based on a recommendation made by Mathias et al (2013b), following a statistical analysis of historical oil and gas production rates in the UK continental shelf. The numerical models employ a radial grid, discretized using 200 equal intervals in log 10 space, from r w to r e .…”
Section: Numerical Solutionsmentioning
confidence: 99%